2022
DOI: 10.1159/000521294
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Histological Effects of Topical Epidermal Growth Factor on Acne and Acne Scars

Abstract: <b><i>Background:</i></b> The inflammatory lesions of acne leave scars which greatly affect patients’ quality of life. Treatment options targeting both acne and acne scars are still lacking. <b><i>Objectives:</i></b> To evaluate the clinical efficacy of epidermal growth factor ointment (EGFO) on acne and acne scars. <b><i>Methods:</i></b> The study design was 12-week, prospective, split-face, single-blinded. The 36 patients with mild to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…[42][43][44] More recently, a split-face study of 36 patients with mild-to-moderate acne demonstrated that topical application of rhEGF significantly reduced the acne lesions and scar counts, with decreased IGA and ECCA scar grades. 45 Additionally, rhEGF increased the expression of TGF-β1, elastin, and collagen type 1 and 3, and decreased keratin 16, NF-κB p65, IL-1α, and IL-8 expression, which implies that rhEGF has anti-inflammatory properties. 45 Collectively, these studies suggest that rhEGF may be a possible therapeutic adjuvant for both acne and acne scarring.…”
Section: Acnementioning
confidence: 91%
See 1 more Smart Citation
“…[42][43][44] More recently, a split-face study of 36 patients with mild-to-moderate acne demonstrated that topical application of rhEGF significantly reduced the acne lesions and scar counts, with decreased IGA and ECCA scar grades. 45 Additionally, rhEGF increased the expression of TGF-β1, elastin, and collagen type 1 and 3, and decreased keratin 16, NF-κB p65, IL-1α, and IL-8 expression, which implies that rhEGF has anti-inflammatory properties. 45 Collectively, these studies suggest that rhEGF may be a possible therapeutic adjuvant for both acne and acne scarring.…”
Section: Acnementioning
confidence: 91%
“…During a 12‐week trial, Ronald et al demonstrated the beneficial effects of topical rhEGF in acne scarring by showing how the mean investigator global assessment (IGA) score and the Goodman grade—a qualitative scar grading system for acne scarring—improved with rhEGF treatment 42‐44 . More recently, a split‐face study of 36 patients with mild‐to‐moderate acne demonstrated that topical application of rhEGF significantly reduced the acne lesions and scar counts, with decreased IGA and ECCA scar grades 45 …”
Section: Acnementioning
confidence: 99%
“…have demonstrated that EGFO effectively improves acne vulgaris and scars clinically and histologically. In addition, they found that EGFO can reduce inflammation and abnormal keratinization and promote scar regeneration through immunohistochemical analysis 96 …”
Section: Emerging Therapiesmentioning
confidence: 99%
“…96 Recent studies have shown that exosomes derived from human adipose tissue stem cells (ASCE) have stem cell key features and are as effective as MSCs in repairing various organ injuries 97,98. Hyuck Hoon KWON et al studied the efficacy of carbon dioxide fractional laser combined with exosomes (derived from adipose tissue stem cells) in…”
mentioning
confidence: 99%
“…Acne vulgaris (AV), a prevalent dermatological ailment, can affect the face, neck, chest, back, and shoulders, among other pilosebaceous regions. The main clinical symptoms of AV include seborrheic, non-inflammatory skin lesions, inflammatory lesions, and scarring of varying degrees 1 2 . Over 85% of young individuals worldwide are affected by AV, and symptoms can linger into adulthood 3 .…”
Section: Introductionmentioning
confidence: 99%